Effects of Forest Management on the Insect Assemblage of Black Cherry (Prunus serotina) in the Allegheny National Forest - Craig Larcenaire; Fumin Wang; Ida Holásková; Richard Turcotte; Michael Gutensohn; Yong-Lak Park (Plants, 2022)
Over the last decade, the Allegheny National Forest (ANF) in the USA has experienced issues with the regeneration of black cherry (Prunus serotina). This study was conducted to investigate the effects of silvicultural treatment on the insect communities that may affect black cherry pollination and regeneration. We conducted a 2-year study to compare the abundance, richness, and diversity of insects in unmanaged, shelterwood seed-tree, and shelterwood clear-cut stands. Using pan traps, we sampled insects at the ground level and in the canopies of flowering mature black cherry trees. The results of this study showed significant increases in the abundance of insects captured in shelterwood seed-tree stands and in species richness and diversity of insects captured in the canopy of black cherry in shelterwood removal stands, indicating that silvicultural treatment affected the insect community significantly. The dominant insect order was Diptera (true flies, 72.91%, n = 12,668), and Anthalia bulbosa (Diptera: Hybotidae) was the dominant species comprising 33% of all insects found in the canopy of flowering black cherry. The findings in this study could help land managers in managing black cherry for its pollination and natural regeneration.